Analisis Pengaruh Pengawasan BPD Terhadap Efektivitas Pengelolaan Dana Desa Tahun 2023 di Desa Selojari Kabupaten Grobogan - Agus Bahrudin (Universitas 17 Agustus 1945, 2024)
This research aims to analyze the influence of supervision by the Village Consultative Body (BPD) on the effectiveness of Village Fund management in 2023 in Selojari Village, Grobogan Regency. This research used the Explanatory Research type involving 70 respondents selected through proportional random sampling. Data was collected through direct observation, interviews and questionnaires, then analyzed using qualitative and quantitative methods. The research results show that the Selojari Village BPD has good abilities in carrying out supervision, including in creating supervision standards, understanding the activities being supervised, comparing results with standards, and conducting evaluations. The majority of respondents stated that village development planning involved the community, the Village Fund budget was quite clear in its allocation, and the implementation of activities involved the implementation team. Statistical analysis using product moment correlation produces a calculated r of 0.664, which is greater than the r table (0.235) at the 5% confidence level. This shows that there is a positive and significant influence between BPD supervision on the effectiveness of Village Fund management in Selojari Village. This research concludes that the supervisory role of BPD is very important in increasing the effectiveness of Village Fund management, so efforts are needed to strengthen the capacity of BPD and increase community participation in the supervision process.